2000
DOI: 10.1097/00000542-200006000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Fluid Removal during Cell Salvage in the Cesarean Section Patient

Abstract: Leukocyte depletion filtering of cell-salvaged blood obtained from cesarean section significantly reduces particulate contaminants to a concentration equivalent to maternal venous blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
142
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(145 citation statements)
references
References 28 publications
1
142
0
2
Order By: Relevance
“…This technique involves suctioning of blood from the operative field followed by cell washing, suspension in saline, and reinfusion to the patient [24]. Concerns about its possible association with amniotic fluid embolism (AFE) have made this technique controversial [25][26][27].…”
Section: Intraoperative Cell Salvagementioning
confidence: 99%
See 2 more Smart Citations
“…This technique involves suctioning of blood from the operative field followed by cell washing, suspension in saline, and reinfusion to the patient [24]. Concerns about its possible association with amniotic fluid embolism (AFE) have made this technique controversial [25][26][27].…”
Section: Intraoperative Cell Salvagementioning
confidence: 99%
“…Fetal squamous cells, meconium, and other particulates have also been implicated in the development of AFE [30]. Waters and colleagues [26] demonstrated that when cells are washed and a leukocyte depletion filter is used, the resulting blood has a concentration of fetal squamous cells similar to a preoperative maternal blood sample [26].…”
Section: Intraoperative Cell Salvagementioning
confidence: 99%
See 1 more Smart Citation
“…Cell salvage has been used in obstetrics to a limited degree because of the fear of amniotic fluid embolism although the exact mechanism is still unclear. In contrast, leukocyte depletion filtering of cell-salvaged blood obtained from cesarean section reduces amniotic fluid components to a concentration equivalent to maternal venous blood (9). This device has been reportedly used safely in !400 cases (4,10).…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the quality of blood that would be returned to the mother, if cell salvage had been used at caesarean section, have shown that there is no safety concern with modern equipment as amniotic fluid is both effectively and completely removed by cell salvage processing. 27,28 Despite concerns about AFE as a consequence of cell salvage having proven unfounded in research thus far, 27,28 and evidence that the transfer of amniotic fluid into the maternal circulation is a common event that does not necessarily cause adverse effects, [29][30][31][32] this issue remains of concern to clinicians.…”
Section: Cell Salvage In Caesarean Sectionmentioning
confidence: 99%